EXPERT SYSTEM FOR DETECTING DISEASES OF PALM OIL WITH FORWARD CHAINING METHOD ANDROID BASED - Basmallah Ramadhani Aisyah Putri; Ainul Rhozy Ichwanto; Imelda Imelda (STMIK Royal, 2023)
Abstract : Coconut plantation palm has a very strategic role in the development of the Indonesian economy. Coconut palm that is processed becomes oil cook and material burn. To produce product quality derivatives from coconut palm this needs proper handling in its maintenance. On plantation coconut palm lots were found to cause coconut infected palm disease, so this will hinder productivity of the plantation. Handling is not appropriate to coconut infected palm disease and can result in losses that don't little. To overcome the problem, they make it a system android based expert. System experts can diagnose disease with detect the symptoms shown coconut palm moment attacked disease, so taking decision for handling furthermore will be more accurate that will impact on results maximum harvest. Keywords : android; coconut palm; disease; system expert. Abstrak : Perkebunan kelapa sawit memiliki peranan yang sangat strategis dalam pembangunan ekonomi Indonesia. Kelapa sawit ini banyak diolah menjadi minyak masak dan bahan bakar. Untuk menghasilkan produk turunan yang berkualitas dari kelapa sawit ini maka membutuhkan penanganan yang tepat dalam pemeliharaannya. Pada perkebunan kelapa sawit banyak ditemukan kasus kelapa sawit yang terserang penyakit, sehingga hal ini akan menghambat produktivitas perkebunan. Penanganan yang tidak tepat terhadap kelapa sawit yang terserang penyakit dapat mengakibatkan kerugian yang tidak sedikit. Untuk mengatasi masalah tersebut dibuatlah sistem pakar yang berbasis android. Sistem pakar dapat mendiagnosis penyakit dengan mendeteksi gejala-gejala yang ditunjukan kelapa sawit saat terserang penyakit, sehingga pengambilan keputusan untuk penanganan selanjutnya akan lebih akurat yang akan berdampak pada hasil panen yang maksimal. Kata Kunci : android; kelapa sawit; penyakit; sistem pakar.